1191. Comparison of High Touch Surface Bioburden Associated with the Use of Disinfectants With and Without Continuously Active Disinfection Properties in Ambulatory Care Settings. (15th December 2022) - Torres, Heidi M; Marino, Jamie; Simon, Matthew; Singh, Harjot K; Westblade, Lars; Calfee, David P
Abstract: Background: Microbial contamination of high-touch surfaces (HTS) in health care settings contributes to pathogen transmission. HTS quickly become re-contaminated after disinfection. A quaternary ammonium (QA) and isopropyl alcohol (IPA)-based disinfectant (Sani-24®) with reported continuously active disinfection (CAD) properties for up to 24 hours has been associated with reduced microbial buildup on HTS over time in in vitro studies and inpatient healthcare settings. The performance of this product in ambulatory care settings has not been reported. Methods: HTS bioburden associated with use of QA-IPA with CAD (Sani-24®) was compared to that of a QA-IPA disinfectant without CAD (Super Sani-Cloth®) in an urgent care center (UCC) and outpatient clinic (OPC). Surfaces/rooms were assigned 1:1 to the disinfectants. Study team used pre-saturated wipes to disinfect designated HTS (stretcher/exam table, stretcher rail, armrest, doorknob, counter, light switch) at the beginning of each sampling period. In the UCC, unit staff performed subsequent disinfection per routine protocols. In the OPC, unit staff used the study-assigned disinfectant for disinfection between patients. HTS were sampled at 0, 4-6, 8-12, and 24 hours using Eswabs soaked in neutralizing broth. Microbial burden was quantified after 48 hours of incubation. Average CFU/cm² were compared using T-tests and proportion of samples with < 2.5 CFU/cm², a microbiologic standard for environmental surfaces, were compared by chi-square test. Results: 66 UCC HTS (33 per disinfectant) and 70 OPC HTS (35 per disinfectant) were included. There were no statistically significant differences in average CFU/cm² on individual HTS (Figure 1) or average CFU/cm² on all HTS combined between the disinfectants. There were also no significant differences in the proportion of surfaces with < 2.5 CFU/cm² (Figure 2) between the disinfectants. Conclusion: No differences were observed in the HTS bioburden in ambulatory settings over 24 hours following disinfection using products with and without CAD. These findings differ from those of studies in other settings, perhaps due to frequent disinfection, less extensive recontamination, or Hawthorne effect in these ambulatory settings. Further study in other ambulatory care settings is warranted. Disclosures: Harjot K. Singh, MD, clinical care options: Advisor/Consultant|MJSciences/HCP Live: Advisor/Consultant|NYC Health and Hospitals: Advisor/Consultant Lars Westblade, PhD, Accelerate Diagnostics, Inc.: Grant/Research Support|BioFire Diagnostics, LLC: Grant/Research Support|Hardy Diagnostics: Grant/Research Support|Roche Molecular Systems, Inc.: Advisor/Consultant|Roche Molecular Systems, Inc.: Grant/Research Support|Shionogi, Inc.: Advisor/Consultant|Talis Biomedical: Advisor/Consultant.